COVID-19 and Youth Psychopathological Distress in Umbria, Central Italy: A 2-Year Observational Study in a Real-World Setting - Menculini, Giulia; Pomili, Giorgio; Brufani, Francesca; Minuti, Agnese; Mancini, Niccolò; D’Angelo, Martina; Biscontini, Sonia; Mancini, Enrico; Savini, Andrea; Orsolini, Laura; Volpe, Umberto; Tortorella, Alfonso; et al. (Frontiers in Psychiatry, 2022)
Introduction Adolescents and young adults represent a vulnerable population in the context of the Coronavirus disease 2019 (COVID19) pandemic. The aim of the present retrospective study is to investigate the psychological impact of the pandemic on adolescents and young adults, by analyzing data from an outpatient mental health service dedicated to youths in Umbria, central Italy. Materials and Methods The clinical charts of subjects aged 14-24 who first accessed the service in the timeframe between March 1st, 2019 and March 1st, 2021 were reviewed. Subjects were divided into two subgroups according to the period of time when they accessed the service (pre-COVID-19 vs post-COVID-19 outbreak). Bivariate analyses were performed using the Chi-square test and the Student’s t-test (p<0.05). A secondary analysis was performed considering only subjects suffering from psychiatric disorders. Furthermore, data concerning individuals who were already followed by the service before the pandemic were analyzed by the McNemar’s test and the t-paired test in order to assess changes in treatment features. Results The number of new accesses during the pandemic period remained essentially stable. Youths accessing the service after the emergency onset showed a higher prevalence of anxiety disorders (p=0.022). In the post-COVID-19 period, services were more frequently delivered by using a telepsychiatry approach (p=0.001). Psychopharmacological treatment was more frequently prescribed among subjects that were referred to the service after the pandemic (p=0.033). As for substance use, a statistically significant reduction in opioid use was observed (p=0.003). In the subpopulation of subjects suffering from psychiatric disorders, family therapy was delivered less frequently in the post-COVID-19 subgroup (p=0.013). When considering subjects who referred to the service in the pre-COVID-19 period, the number of interventions provided to this population significantly increased after the pandemic outbreak (p=0.038). Discussion Data from the present study confirm that youths represent an at-risk population for which pathways to care should be reinforced and targeted interventions, including psychosocial treatments, should be proposed.